SimPaths: An open-source microsimulation model for life course analysis - Patryk Bronka; Justin van de Ven; Daniel Kopasker; Srinivasa Vittal Katikireddi; Matteo Richiardi (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2023)
SimPaths is a family of models for individual and household life course events, all sharing common components. The framework is designed to project life histories through time, building up a detailed picture of career paths, family (inter)relations, health, and financial circumstances. It builds upon standardised assumptions and data sources, which facilitates adaptation to alternative countries – versions currently exist for the UK and Italy, and are under development for Hungary, Poland and Greece. Careful attention is paid to model validation, and sensitivity of projections to key assumptions. The modular nature of the SimPaths framework is designed to facilitate analysis of alternative assumptions concerning the tax and benefit system, sensitivity to parameter estimates and alternative approaches for projecting labour/leisure and consumption/savings decisions. Projections for a workhorse model parameterised to the UK context are reported, which closely reflect observed data throughout a validation window between the Financial crisis (2011) and the Covid-19 pandemic (2019).
Keywords: 330; Life Course Analysis; Microsimulation; Households